PELAKSANAAN BIMBINGAN PERKAWINAN BAGI CALON PENGANTIN PERSPEKTIF MASLAHAH MURSALAH (Studi Kasus di Kantor Urusan Agama Kecamatan Balerejo Kabupaten Madiun) - Siti Qomariah; Kadenun Kadenun; Diyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The existence of the pre-marital marriage guidance process is very important for the formation of the samawa family, the purpose of marriage and the importance of the perspective of maslahah mursalah in the marriage and the realization of a harmonious, peaceful and prosperous society both materially and spiritually, so that the problem formulation in this thesis is: 1 ) How is the implementation of Marriage Guidance for prospective brides at KUA, Balerejo District, Madiun Regency? 2) What is the perspective of maslahah mursalah on the implementation of Marriage Guidance for prospective brides at KUA Balerejo District, Madiun Regency? This study used a descriptive qualitative approach, with the type of research being case study research, located at the Office of Religious Affairs, Balerejo District, Madiun Regency. The data used were obtained from interviews, observation and documentation using qualitative data analysis techniques and checking the validity of the data obtained. Based on the results of the research, it was concluded that: 1) the implementation of marriage guidance for prospective brides of marriageable age is divided into 2 types, namely indirect guidance and face-to-face guidance (regular) conducted for 6 hours of lessons for 1 day with a minimum number of participants 10 pairs of prospective brides. 2) From the maslahah mursalah perspective on implementation From the maslahah mursalah perspective on the implementation of Marriage Guidance for prospective brides and grooms at KUA Balerejo District, Madiun Regency, in terms of law in Indonesia and according to the Shari'a and its continuity is relevant and in accordance with the rules and laws in our country.